Evaluation of websites reached using Google in the modern digital era related to approach to cholesterol - Mert İlker Hayıroğlu; Göksel Çinier; Nurgül Keser; Mehmet Uzun; Ali Karagoz; Ali Serdar Fak; Ertugrul Okuyan; Can Altundaş; Ilker Tekkesin (KARE Publishing, 2020)
Objective: The Google search engine is widely used as a source of medical information; however, legal and medical governance of the accuracy of the content retrieved is lacking. The aim of this study was to assess the most read Turkish-language texts related to cholesterol during a specific period according to the validity of the content. Methods: Google Trends was queried on January 5, 2019 for the search term 'cholesterol' and the 9 other most popular search phrases used in Turkey that included the word cholesterol. In all, 100 links were obtained for each phrase, generating a total of 1000 links. Once duplicates were eliminated, a total of 604 links was used for the study. Since there is currently no validation scoring system for this purpose in the literature, the authors created a checklist according to well-accepted recent guidelines focused on cholesterol. The content of the texts acquired was classified as misleading, insufficient but favorable, or sufficient and favorable. Results: The source of the online texts studied was universities (n=8, 1.3%), hospitals (n=6, 0.9%), personal blogs (n=200, 33.1%), health websites (n=183, 30.2%), and medical journals (n=207, 34.2%). In all, 235 texts (38.9%) were classified as sufficient and favorable and 35 (5.7%) were categorized as misleading. A medical practitioner was named in 378 texts (62.5%). All of the results from universities and hospitals were ranked in the favorable group. A statistical difference in the word count was seen in a comparison of the misleading and favorable texts. Conclusion: Google can connect users to a significant quantity of material related to cholesterol that includes a wide range from misleading information to sufficient and favorable texts. The variation in the quality of the content on websites accessible via Google necessitates that cholesterol resource material should be selected with great care.